(untitled) (Journal of Forensic Medicine & Toxicology, 2022)
The title ‘Textbook of Forensic Histopatholgy” fascinated me, more in Indian context. Therefore as soon as I learnt that such book is coming, I booked it. On the due date the book arrived. Believe me; it took me a week to go through topic by topic and page by page. I commonly do so with any new edition I lay my hand on.